Fractality in coffee bean surface for roasting process. (June 2017) - Gabriel-Guzmán, Mauricio; Rivera, Victor M.; Cocotle-Ronzón, Yolanda; García-Díaz, Samuel; Hernandez-Martinez, Eliseo
Highlights: The roasting is the stage where the coffee bean obtained its typical sensory characteristics. Generally, the roasting process is only performed by operator experience. Fractal analysis of coffee beans images provides qualitative information of roasting degree. Image analysis can be used as an inexpensive and easy qualitative tool for coffee roasting monitoring. Abstract: The roasting is the stage where the coffee bean undergoes physiochemical changes that provide their typical sensory characteristics (i.e., aroma and flavor). Despite the importance, the roasting process is performed based on the operator experience, which makes difficult the homogenization between batches of roasted coffee. In that sense, this paper proposes a methodology to analyze changes in the coffee bean during roasting; this can be used as an indicator of the roasting degree. The proposal is based on R/S fractal analysis of coffee bean surface images taken during the roasting process. The results indicate that the Hurst exponent exhibits dynamic changes that can be correlated with the physical changes of the coffee bean, such as fractures and color changes, suggesting that the fractal index could be used for indirect monitoring of the roasting degree.